Biocatalytic Dynamic Kinetic Resolution for the Synthesis of Atropisomeric Biaryl N‐Oxide Lewis Base Catalysts. (9th August 2016) - Staniland, Samantha; Adams, Ralph W.; McDouall, Joseph J. W.; Maffucci, Irene; Contini, Alessandro; Grainger, Damian M.; Turner, Nicholas J.; Clayden, Jonathan
Abstract: Atropisomeric biaryl pyridine and isoquinoline N‐oxides were synthesized enantioselectively by dynamic kinetic resolution (DKR) of rapidly racemizing precursors exhibiting free bond rotation. The DKR was achieved by ketoreductase (KRED) catalyzed reduction of an aldehyde to form a configurationally stable atropisomeric alcohol, with the substantial increase in rotational barrier arising from the loss of a bonding interaction between the N‐oxide and the aldehyde. Use of different KREDs allowed either the M or P enantiomer to be synthesized in excellent enantiopurity. The enantioenriched biaryl N‐oxide compounds catalyze the asymmetric allylation of benzaldehyde derivatives with allyltrichlorosilane.